Building Communicative and Social Skills in an Adolescent with ASD Using Electronic Technologies (Gadgets) - A.R. Burtseva; S.S. Andreev (Moscow State University of Psychology and Education, 2023)
The use of mobile technologies in the field of behavioral intervention in children and adolescents with ASD is becoming an increasingly common strategy. Smartphones, tablets, laptops, etc. allow specialists to create a highly motivating environment, as well as to provide the most accessible and comfortable format for giving information, which has a beneficial effect on the quality of behavioral interventions. In September 2021 on the basis of the Dobry resource center, which provides comprehensive support for families raising children with ASD, the CyberNETiki project was implemented, aimed at teaching adolescents with ASD to communicate in an Internet chat. This article details the project’s methodology and primary results using student N data as an example. It also demonstrates an example of a short preliminary parental questionnaire designed to measure the level of gadget proficiency among adolescents with ASD. Our results show that the use of computer-mediated communication methods can be highly motivational and effective for developing literacy, speech and communication skills. It was revealed that teaching communication in a group format (online chat) can further contribute to improving adolescents’ communication skills due to peer imitation.